Presence of additional head of pronator teres muscle and associated neurovascular variations: a rare case report - Sushma, RK; Srinivasa, RS; Kumar, MR Bhat (Department of Surgery, UKM Medical Centre, 2012)
Arm is a site for frequent injuries and it is involved in many surgical procedures. Variations in the arm have immense clinical significance. During the dissection of a right upper limb, brachial artery was found to divide into radial and ulnar arteries, 3cm above the inter-epicondylar plane. The ulnar artery and the median nerve were then passing through a tunnel formed by an extensive additional humeral head of the pronator teres muscle. Two centimetres long fibromuscular tunnel formed by the humeral head of the pronator teres was found to arise from the medial intermuscular septum and also from the fibrous arch form the shaft of the humerus to the medial intermuscular septum. In the same cadaver, the superior ulnar collateral artery was found to arise from the profunda brachii artery which is otherwise a branch of the brachial artery. Accurate knowledge of these variation patterns is of considerable clinical significance in conduct of surgeries of arm, fracture management of humerus and diagnosis of various compressive neuropathies.